2014
DOI: 10.1002/14651858.cd007669.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Steroid avoidance or withdrawal for pancreas and pancreas with kidney transplant recipients

Abstract: There is currently insufficient evidence for the benefits and harms of steroid withdrawal in pancreas transplantation in the three RCTs (144 patients) identified. The results showed uncertain results for short-term risk of rejection, mortality, or graft survival in steroid-sparing strategies in a very small number of patients over a short period of follow-up. Overall the data was sparse, so no firm conclusions are possible. Moreover, the 13 observational studies findings generally concur with the evidence foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
0
22
0
3
Order By: Relevance
“…Each of these is a potential obstacle after SPK [ 23 ]. A recent Cochran review evaluated steroid avoidance and steroid withdrawal protocols in pancreas transplant recipients [ 24 ]. The authors concluded there is insufficient evidence to support steroid avoidance/withdrawal (both early and late) in available studies of pancreas transplantation, most of which involved SPKs.…”
Section: Advances In Immunosuppressionmentioning
confidence: 99%
“…Each of these is a potential obstacle after SPK [ 23 ]. A recent Cochran review evaluated steroid avoidance and steroid withdrawal protocols in pancreas transplant recipients [ 24 ]. The authors concluded there is insufficient evidence to support steroid avoidance/withdrawal (both early and late) in available studies of pancreas transplantation, most of which involved SPKs.…”
Section: Advances In Immunosuppressionmentioning
confidence: 99%
“…In comparison with registry data, this represents quite a low number. 21 However, it did not unnecessarily increase the rejection rate, as reported by other authors, 22 and may even have prevented some of the undesirable metabolic effects attributed to sirolimus therapy. 17,23 Throughout the study, tacrolimus and sirolimus dose were quite stable with trough levels, usually not exceeding 10 ng/mL.…”
Section: Discussionmentioning
confidence: 58%
“…‹mmünosüpresif tedavide sıklıkla steroid kullanılmaktadır ve bu tedavinin di¤er tedavi seçenekleri ile de¤itirilmesi gereklili¤i tam olarak açık de¤ildir. [10] Di¤er yandan da kullanılan immünosüpresif tedaviye ba¤lı oluabilecek diyabet varlı¤ı da di¤er bir sorundur.…”
Section: Pankreas Nakl‹ End‹kasyonlarıunclassified